Manual de encuentros formativos para jóvenes coordinadores del Movimiento Juvenil Colmena Salesianas - Jiménez Pesántez, María Esther (2015)
This document shows to the young Christians and Salesians how to be an agent of change for the leadership and the evangelization to transform their lives and their communal surrounding. This manual demonstrates the tools for personal growing in all dimensions, confronting talents and limitations to be able to discover God and his deep love for us. The Salesian’s Colony is fed by the Lord’s word and from the unlimited richness of the human being that translates in surprise and novelty in the spirituality on a daily basis. Each developed training space presents a unique principle about Jesus style leadership, a systematic process full of values that will re-launch the practice of interrelation with others in the real world. The training meetings presented, respond to the basic needs of the nowadays youth who are in a permanent research of a superior being and have a incredible social sensibility. This manual is an excellent guide for the personal development and to strengthen the importance of the Colony coordinators. The key that goes through the space for love, light, live, meeting, research and giving is the hope with which men and women can’t live a second without. It is important to communicate the good and happy Jesus-Christ news, and this is what matters to be a Christian and Salesian leader. This is an important resource, of self-help that should be known and used in every moment of our lives. Today, is where you could begin a journey of communal leadership in harmony with nature, cosmos and the new sceneries that society offers to the humanity.